Beyond Acute Kidney Injury : Direct Pathways Implicate Inflammatory Mechanisms in Serum NGAL’s Mortality Effect in Acute Brain Injury - Hyung Seok Guk; Yong Soo Kim; Dong-Wan Kang; Sang-Hoon Han; Museong Kim; Moon-Ku Han; Kyoungho Suk; Jae-Hong Kim; Han-Gil Jeong (Translational Stroke Research, 2026)

Impact of selective iron removal by DIBK-based multistage solvent extraction on radionuclide measurement accuracy in Fe-rich metal matrices - Sang-Jun Han; Bo-Gil Kim; Seung-Gwan Han; So-Yun Jang (Next Research, 2026)

Circadian-dependent UV-B stress responses reveal differential antioxidant and photoprotective mechanisms in Achyranthes japonica microgreens - Ye Lin Kim; Han-Sol Sim; Jae Gil Yun; Ki-Ho Son (Molecular & Cellular Toxicology, 2026)

Recovery of critical metals from circular resources via matte smelting: Process fundamentals and techno-economic boundaries - Joon Sung Choi; Min Seok Seo; Jin Gyun Park; Kwang Sun Woo; ByungWon Kim; Gil Soo Han (Resources, Conservation and Recycling, 2026)

Bio-Fenton reaction system facilitated by the H2O2-producing Desemzia sp. strain C1 degrades sulfonated polyethylene to oxalate - Yongseok Ko; Sunil Ghatge; Youri Yang; Cuong Tu Ho; Dongfei Han; Sujin Lee; Hor-Gil Hur (Journal of Environmental Management, 2026)

A Novel Strain Bifidobacterium longum subsp. longum HN001 Ameliorates High-Fat Diet-Induced Obesity in Mice Through Microbiome-Associated Short-Chain Fatty Acids - Chae Hwan Lee; Youngji Han; Joo Young Ryu; Minseo Jung; Chae Rin Park; Mi Ran Jang; Youn Gil Kwak; Hanvit Cha; Jin Hyup Lee (Probiotics and Antimicrobial Proteins, 2026)

Fuel concentration directs the reaction path of methane oxidation over Pt-ceria catalyst - Siwon Lee; Hyuk Choi; Seunghyun Kim; Ju Hyeok Lee; Yoonseok Choi; Jeong Do Yoo; Minsu Park; Han Gil Seo; Ki-jeong Kim; Ethan J. Crumlin; Beomgyun Jeong; Hyun You Kim; et al. (Chemical Engineering Journal, 2026)

Sustainable production of 1-octanol using biomass-derived acetone and furfural - Seungjun Choi; Jiyun Yoo; Yoonjae Lee; Young-Woong Suh; Jeong Gil Seo; Jeehoon Han (Chemical Engineering Journal, 2026)

Bisphenol AF induces mouse spermatogonia apoptosis via reactive oxygen species-mediated Beclin-1 cleavage - Hyo Jin Gu; Gil Un Han; Seul Gi Kim; Sung-Hwan Moon; Seung Hee Shin; Buom-Yong Ryu (Toxicological Research, 2026)

Genotype analysis of severe fever with thrombocytopenia syndrome viruses in Gyeonggi Province of South Korea from 2017 to 2022 - Han-Gil Cho; Bo-yeon Kweon; Wantae Kim; Minseong Kim (Archives of Virology, 2025)

Suppressing grain growth and thermo-chemical decomposition of perovskite oxide nanoparticles via B-site cation surface stabilization - Nikolai Tsvetkov; Han Gil Seo; Jongsu Seo; Bonjae Koo; Hyunseung Kim; Keon-Han Kim; Sejong Ahn; Jeung Ku Kang; WooChul Jung (Chemical Engineering Journal, 2025)

Triflumizole induces excessive reactive oxygen species, inhibits the GPR30/PI3K/AKT pathway, and triggers apoptosis and autophagy in GC-1 spermatogonia cells - Seul Gi Kim; Dong-Jin Yoon; Daniel Chavez Varias; Gi Jeong Ahn; Gil Un Han; Sung-Hwan Moon; Hee-Seok Lee; Seung Hee Shin; Buom-Yong Ryu (Pesticide Biochemistry and Physiology, 2025)

Platycodin D reverses tumor necrosis factor-α-induced endothelial dysfunction by increasing nitric oxide through G protein-coupled estrogen receptor-mediated eNOS activity - Ju Yeon Chae; Gi Ho Lee; Seung Yeon Lee; Gil-Saeng Jeong; Hwi-yeol Yun; Eun Hee Han; Anh Thi Ngoc Bui; Hye Gwang Jeong (Chemico-Biological Interactions, 2025)

Polyhexamethylene guanidine-phosphate enhances pro-coagulant activity of human erythrocytes and venous thrombosis in rats through phosphatidylserine externalization - Sungbin Choi; Eun-Hye Kim; Donghyun Kim; Han Jin Park; Junkyung Gil; Yiying Bian; Ok-Nam Bae (Journal of Hazardous Materials, 2025)

Yolk-shell nanoparticle-loaded multifunctional membrane with photothermal and advanced oxidation properties - Geun Young Kim; Jeong-Min Park; Hyun-Seok Choe; Han-Gil Kim; Suyoung Jeong; Jae-Hong Kim; Jae-Hyuk Kim (Chemical Engineering Journal, 2025)

Effects of environmental and physical factors on the shell infiltration density of free-living conchocelis of three Pyropia species (Bangiales, Rhodophyta) - Jin Suk Heo; Jang Kyun Kim; Han Gil Choi (Algae, 2024)
Shell infiltration of free-living conchocelis of the three commercial Pyropia species ( P. yezoensis , P. seriata , and P. dentata ) were examined in various conditions of temperatures (20–25°C), light intensities (1, 10, 40, and 80 μmol photons m -2 s -1 ), conchocelis quantities (100, 150, 200, 250, and 300 mg) and sizes (108, 209, 324, 411, and 519 μm). The optimal shell infiltration conditions were 20°C and 40 μmol photons m -2 s -1 in all species. The infiltration densities were 44.81–146.15 conchocelis cm -2 for P. yezoensis , 51.40–190.49 conchocelis cm -2 for P. seriata , and 22.24–92.49 conchocelis cm -2 for P. dentata . Inefficient shell infiltration was observed with the different conchocelis quantities from 100 to 300 mg. A positive corelationship was observed between shell infiltration density and the amount of conchocelis. The optimal blending time for maximizing infiltration density was 40 s for P. yezoensis and P. seriata and 25 s for P. dentata . This blending time correlated with a cell count of 5–7 cells. Total conchocelis lengths of 5–7 cells were approximately 300 μm for P. yezoensis and P. seriata (with cell size of about 45 μm) and approximately 400 μm for P. dentata (with a cell size of about 65 μm). These results suggest that, to achieve optimal shell infiltration density for P. dentata , the blending time should be reduced by half, and the amount of conchocelis should be increased twofold, making it comparable to the other two Pyropia species.

Eco-friendly biocontrol of pine wilt disease: Enhancing tree defense with Bacillus subtilis JCK-1398 for sustainable forest management - Mohamed Mannaa; Ae ran Park; Jungwook Park; Hee Won Jeon; Hyejung Jung; Hyo Seong Jeon; Gil Han; Jin-Cheol Kim; Young-Su Seo (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Development of polymorphic simple sequence repeat markers in Agastache rugosa and their application in genetic evaluation and cross-taxon transferability of Agastache species - Hye Ran Shin; Ick Hyun Jo; Raveendar Sebastin; Jinsu Gil; Gi Yeong Kim; Suyun Moon; Hyun-Seung Park; Sewon Oh; Jong Won Han; Kyung Ho Ma; Yi Lee; Daeil Kim; et al. (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Diisobutyl phthalate (DiBP)-induced male germ cell toxicity and its alleviation approach - Seok-Man Kim; Yong-Hee Kim; Gil Un Han; Seul Gi Kim; Dong Ha Bhang; Byung-Gak Kim; Sung-Hwan Moon; Seung Hee Shin; Buom-Yong Ryu (Food and Chemical Toxicology, 2024)

Modeling ozone deposition on bulk grains and ozone deposition in columns of wheat grains - Su Gil Kim; Un Yong Paek; Ae Chun Ri; Song Ho Kim; Il Song Han; Songchol Hong (Journal of Stored Products Research, 2023)

Behavior of lightweight-foamed soil reinforced by waste fishing net and its design guideline - Jinung Do; Sun-Bin Kim; Taek-Hee Han; Gil-Lim Yoon (Marine Georesources & Geotechnology, 2023)

Butylparaben promotes phosphatidylserine exposure and procoagulant activity of human red blood cells via increase of intracellular calcium levels - Yeonju Ko; Eun-Hye Kim; Donghyun Kim; Sungbin Choi; Junkyung Gil; Han Jin Park; Yusun Shin; Wondong Kim; Ok-Nam Bae (Food and Chemical Toxicology, 2023)

Single atomic Fe-based honeycomb catalysts with hierarchically ordered meso- and macropore for the oxygen reduction reaction - Han-Wool Jang; Gil-Seong Kang; Jong Yoon Lee; Seon Yeong Lee; Gwanwon Lee; Sung Jong Yoo; Sungho Lee; Han-Ik Joh (Chemical Engineering Journal, 2023)

Effect of different vacuum levels for beef brisket during cold storage: A microbiological and physicochemical analysis - Ah-Na Kim; Kyo-Yeon Lee; Chae-Yeon Han; Sung-Gil Choi (Food Microbiology, 2023)

Ecological evaluation of marine macroalgal communities on five islands of Korea in the Yellow Sea - Su Jin Han; Jae-Gil Jang; Hyun-Jung Kim; Tae-Ho Seo; Joo Myun Park (Acta Oceanologica Sinica, 2023)

Development of an Autonomous Cleaning Robot with a Hydraulic Manipulator Arm for the Cleaning of Niche Areas of a Ship Hull - Daegil Park; Jong-Boo Han; Teakyeong Yeu; Su-gil Cho; Seongsoon Kim; Hyungwoo Kim; Yeongjun Lee (Journal of Marine Science and Engineering, 2023)
Fouling organisms reduce a ship’s fuel efficiency and disturb the ecosystem. Therefore, the International Maritime Organization (IMO) and many nations have enacted laws that mandate periodic hull cleaning for removing fouling organisms. However, cleaning niche areas of the ship hull is extremely difficult. Due to their complex shape, applying antifouling paint and cleaning with hull cleaning robots is difficult, but about 80% of fouling organisms are concentrated in the niche areas. To resolve this issue, this research proposes the use of an autonomous cleaning robot with a hydraulic polyarticular robot arm to clean niche areas of the ship hull. This robot can approach niche areas of the ship hull with complex shapes using its polyarticular arm. It was designed to be able to scan the cleaning area, establish a cleaning plan, and clean accordingly. This robot autonomously cleaned a propeller blade, which is a typical niche area of the ship hull, to verify the applicability of this system. The experiment results show that approximately 80% of the biofouling was removed from the hull crevices and 81% of the cleaned biofouling was recovered.

Deciphering Functional Connectivity Differences Between Motor Imagery and Execution of Target-Oriented Grasping - Eunkyung Kim; Woo Hyung Lee; Han Gil Seo; Hyung Seok Nam; Yoon Jae Kim; Min-Gu Kang; Moon Suk Bang; Sungwan Kim; Byung-Mo Oh (Brain Topography, 2023)

Preclinical safety assessment of the suction-assisted intradermal injection of the SARS-CoV-2 DNA vaccine candidate pGO-1002 in white rabbit - Seunghee Oh; Min Seong Jang; Kyung Jin Jung; Ji-Seok Han; Hyojin Lee; Areum Gil; Bohyun Jeon; Christine C. Roberts; Joel N. Maslow; Yong-Bum Kim; Kang-Hyun Han (Archives of Toxicology, 2023)

Metal-oxide nanocomposite catalyst simultaneously boosts the oxygen reduction reactivity and chemical stability of solid oxide fuel cell cathode - SungHyun Jeon; Jongsu Seo; Jeong Woo Shin; Sungje Lee; Han Gil Seo; Siwon Lee; Nikolai Tsvetkov; Jinwook Kim; Jihwan An; WooChul Jung (Chemical Engineering Journal, 2023)

Effect of substratum types on the growth of assimilators and stolons of Caulerpa okamurae (Bryopsidales, Chlorophyta) - Seo Kyoung Park; Jang K. Kim; Han Gil Choi (Algae, 2022)
To examine the effects of substratum types on the growth of Caulerpa okamurae, sand surface and sand burial experiments were conducted. Five assimilators (erect fronds) per replicate were cultured for 15 d on the surface of three different treatments: fine sand (200 μm), coarse sand (600 μm), and no sand (control). Also, three stolons and three assimilators were buried by fine grain or coarse grain sands and incubated for 15 d. In both experiments, other culture conditions included 25°C, 30 μmol photons m-2 s-1, and 16 : 8 h L : D (light : dark). In both experiments, stolon + assimilator-, assimilator-, and stolon-weights were measured. Relative growth rates (RGRs) of stolon + assimilator weights ranged from 0.43 to 1.95% d-1 at no sand and fine sand treatment, respectively. RGRs for the weight of stolon + assimilator and new assimilators were significantly greater on the fine- and coarse sand surface than the control. In the burial experiments, RGRs of stolons (4.28% d-1 at coarse sand and 5.57% d-1 at fine sand, respectively) were significantly greater than those of assimilators (1.38% d-1 at fine sand and 1.82% d-1 at coarse sand, respectively). When stolons were buried, RGRs for assimilators were greater at the fine sand than at the coarse sand treatment. On the other hand, RGRs of buried assimilators for total frond weights and for newly produced stolons were significantly greater at the coarse sands than at the fine sands. In conclusion, C. okamurae grew well with all substrates of sands and showed better growth on fine sands than coarse ones. This result suggests that the growth of stolons and assimilators of C. okamurae is stimulated after stable attachment to the sand substrates by rhizophores. In addition, stolons showed higher growth rates than the assimilators in the sand burial states, indicating that stolons are more tolerant to low light than assimilators of C. okamurae.

The invasive alga Gracilaria vermiculophylla in the native northwest Pacific under ocean warming: Southern genetic consequence and northern range expansion - Yi-Jia Liu; Kai-Le Zhong; Alexander Jueterbock; Shimada Satoshi; Han-Gil Choi; Florian Weinberger; Jorge Assis; Zi-Min Hu (Frontiers in Marine Science, 2022)
Ocean warming is one of the most important factors in shaping the spatial distribution and genetic biodiversity of marine organisms worldwide. The northwest Pacific has been broadly illustrated as an essential seaweed diversity hotspot. However, few studies have yet investigated in this region on whether and how past and ongoing climate warming impacted the distribution and genetic pools of coastal seaweeds. Here, we chose the invasive species Gracilaria vermiculophylla as a model, and identified multiple genetic lineages in the native range through genome-scale microsatellite genotyping. Subsequently, by reconstructing decadal trends of sea surface temperature (SST) change between 1978 and 2018, we found that SST in northern Japan and the East China Sea indeed increased broadly by 0.25-0.4°C/decade. The projections of species distribution models (SDMs) under different future climate change scenarios (RCP 2.6, RCP 4.5, RCP 6.0 and RCP 8.5) indicated that a unique genetic pool of G. vermiculophylla at its current southern range limit (i.e. the South China Sea) is at high risk of disappearance, and that the populations at its current northern range limit (i.e. in Hokkaido region) will undergo poleward expansions, particularly by the year 2100. Such responses, along with this species’ limited dispersal potential, may considerably alter the contemporary distribution and genetic composition of G. vermiculophylla in the northwest Pacific, and ultimately threaten ecological services provided by this habitat-forming species and other associated functional roles.

Concise review of the genus Neopyropia (Rhodophyta: Bangiales) - Hyung-Seop Kim; Han Gil Choi; Mi-Sook Hwang; You Jin Jeon; Charles Yarish; Jang Kyun Kim (Journal of Applied Phycology, 2022)

Low genetic diversity in the endangered marine alga Silvetia siliquosa (Ochrophyta: Fucaceae) and the implication to conservation - Yanshuo Liang; Jie Zhang; Xiaohan Song; Han-Gil Choi; Xu Gao; Delin Duan; Zi-min Hu (Journal of Oceanology and Limnology, 2022)

IL-10 Deficiency Aggravates Renal Inflammation, Fibrosis and Functional Failure in High-Fat Dieted Obese Mice - Dae Hwan Kim; So Young Chun; EunHye Lee; Bomi Kim; BoHyun Yoon; Haejung Gil; Man-Hoon Han; Yun-Sok Ha; Jun Nyung Lee; Tae Gyun Kwon; Bum Soo Kim; Byung Ik Jang (Tissue Engineering and Regenerative Medicine, 2021)
BACKGROUND: High-fat diet-induced obesity is one of the major cause of chronic renal failure. This obesity-related renal failure is mainly caused by inflammatory processes. However, the role of the major anti-inflammatory cytokine interleukin (IL)-10 has not been researched intensively. METHODS: To evaluate the effect of IL-10 deficiency on obesity-related renal failure, the in vivo study was carried with four animal groups; (1) Low-fat dieted C57BL/6 mice, (2) Low-fat dieted IL-10 knockout (KO) mice, (3) High‐fat dieted C57BL/6 mice and (4) High‐fat dieted IL-10 KO mice group. The analysis was carried with blood/urine chemistry, H&E, Oil-Red-O, periodic acid-Schiff and Masson’s trichrome staining immunohistochemistry and real-time PCR methods. RESULTS: At week 12, high‐fat dieted IL-10 KO mice showed 1) severe lipid accumulation in kidneys, cholesterol elevation (in total, serum kidney) and low-density lipoprotein increasion through the SCAP-SREBP2-LDLr pathway; (2) serious histopathologic alterations showing glomerulosclerosis, tubulointerstitial fibrosis and immune cell infiltration; (3) increased pro‐inflammatory cytokines and chemokines expression; (4) enhanced renal fibrosis; and (5) serious functional failure with high serum creatinine and BUN and proteinuria excretion compared to other groups. CONCLUSION: IL-10 deficiency aggravates renal inflammation, fibrosis and functional failure in high-fat dieted obese mice, thus IL-10 therapy could be applied to obesity-related chronic renal failure.

Kelp aquaculture in China: a retrospective and future prospects - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
Globally, China has the largest scale of kelp cultivation and production operations. However, its kelp aquaculture industry is suffering from declining germplasm diversity, degradation of agronomic traits, the presence of polluted environments, changing ocean conditions and increasing anthropological interference. This review covers two of the most commercially important kelp species in China, viz. Saccharina japonica and Undaria pinnatifida . It summarizes the history of their cultivation, production, economic and ecological benefits, their breeding programmes (e.g. inter‐ and intra‐specific hybridization and marker‐assisted selection) and efforts towards population genetic diversity and conservation. The article focuses on three significant challenges, for example genetic cross‐contamination between the wild and farmed kelp populations, ocean warming and ocean acidification. Accordingly, we outline the steps required to provide several intervention measures, for example (i) collection and preservation of wild and cultivated kelp germplasm; (ii) selection of suitable cultivation sites under changing environmental conditions; (iii) developing stress‐resistant cultivars; and finally, (iv) adoption of innovative cultivation models. The review concludes with genome‐based, designs for molecular breeding and calls for the establishment of an East Asian Kelp Consortium (EAKC). Collectively, the Chinese kelp industry could provide beneficial goods and services, for example bioenergy to fine chemicals and environmental benefits, such as carbon capture, pH amelioration and provision of habitat for many other marine species of commercial value. The strategies proposed in this article thus have the potential to not only improve but also reinvigorate the kelp industry in China and nearby Japan and Korea, in the context of both environmental health and economic benefits.

Cover Image - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
The cover image is based on the Review Article Kelp aquaculture in China: A retrospective and future prospects by Zi‐Min Hu et al., https://doi.org/10.1111/raq.12524 . image

MtDNA-Based Phylogeography of the Red Alga Agarophyton vermiculophyllum (Gigartinales, Rhodophyta) in the Native Northwest Pacific - Kai-Le Zhong; Xiao-Han Song; Han-Gil Choi; Shimada Satoshi; Florian Weinberger; Stefano G. A. Draisma; De-Lin Duan; Zi-Min Hu (Frontiers in Marine Science, 2020)

Algal endophytes of commercial Chondrus ocellatus (Gigartinaceae, Rhodophyta) from different wild populations in Korea - Xu Gao; Cyr Abel Maranguy Ogandaga; Seo Kyoung Park; Ji Chul Oh; Han Gil Choi (Journal of Applied Phycology, 2020)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Assessment of optimal growth conditions for cultivation of the edible Caulerpa okamurae (Caulerpales, Chlorophyta) from Korea - Xu Gao; Han Gil Choi; Seo Kyoung Park; Zhong Min Sun; Ki Wan Nam (Journal of Applied Phycology, 2019)

Physiological differences in the growth and maturation of Eisenia bicyclis and Ecklonia cava gametophytes in Korea - Han Gil Choi; Da Vine Jeon; Seo Kyoung Park; Xu Gao (Journal of Oceanology and Limnology, 2019)

Fecal pollution: new trends and challenges in microbial source tracking using next‐generation sequencing - Tatsuya Unno; Christopher Staley; Clairessa M. Brown; Dukki Han; Michael J. Sadowsky; Hor‐Gil Hur (Environmental Microbiology, 2018)
Summary In this minireview, we expand upon traditional microbial source tracking (MST) methods by discussing two recently developed, next‐generation‐sequencing (NGS)‐based MST approaches to identify sources of fecal pollution in recreational waters. One method defines operational taxonomic units (OTUs) that are specific to a fecal source, e.g., humans and animals or shared among multiple fecal sources to determine the magnitude and likely source association of fecal pollution. The other method uses SourceTracker, a program using a Bayesian algorithm, to determine which OTUs have contributed to an environmental community based on the composition of microbial communities in multiple fecal sources. Contemporary NGS‐based MST tools offer a promising avenue to rapidly characterize fecal source contributions for water monitoring and remediation efforts at a broader and more efficient scale than previous molecular MST methods. However, both NGS methods require optimized sequence processing methodologies (e.g. quality filtering and clustering algorithms) and are influenced by primer selection for amplicon sequencing. Therefore, care must be taken when extrapolating data or combining datasets. Furthermore, traditional limitations of library‐dependent MST methods, including differential decay of source material in environmental waters and spatiotemporal variation in source communities, remain to be fully understood. Nevertheless, increasing use of these methods, as well as expanding fecal taxon libraries representative of source communities, will help improve the accuracy of these methods and provide promising tools for future MST investigations.

Correction to: Targeted next-generation sequencing for identifying genes related to horse temperament - Soyoung Song; Dong‑Yep Oh; Gil‑Jae Cho; Dong Hee Kim; Yong‑Soo Park; Kyudong Han (Genes & Genomics, 2018)

Growth, reproduction and recruitment of Silvetia siliquosa (Fucales, Phaeophyceae) transplants using polyethylene rope and natural rock methods - Xu Gao; Han Gil Choi; Seo Kyoung Park; Jung Rok Lee; Jeong Ha Kim; Zi-Min Hu; Ki Wan Nam (Algae, 2017)

Targeted next-generation sequencing for identifying genes related to horse temperament - Soyoung Song; Dong-Yep Oh; Gil-Jae Cho; Dong Hee Kim; Yong-Soo Park; Kyudong Han (Genes & Genomics, 2017)

Detection of waterborne norovirus genogroup I strains using an improved real time RT-PCR assay - Han-Gil Cho; Sung-Geun Lee; Su-Kyoung Mun; Myung-Jin Lee; Po-Hyun Park; Weon-Hwa Jheong; Mi-Hye Yoon; Soon-Yong Paik (Archives of Virology, 2017)

Wart-like spot formation on the fronds of Chondrus ocellatus (Gigartinales) by a brown alga, Mikrosyphar zosterae (Ectocarpales) in Korea - Cyr Abel Maranguy Ogandaga; Yeon Ju Na; Sang-Rae Lee; Young Sik Kim; Han Gil Choi; Ki Wan Nam (Journal of Applied Phycology, 2017)

Oceanic currents drove population genetic connectivity of the brown alga Sargassum thunbergii in the north‐west Pacific - Jing‐Jing Li; Zi‐Min Hu; Xu Gao; Zhong‐Min Sun; Han‐Gil Choi; De‐Lin Duan; Hikaru Endo (Journal of Biogeography, 2017)
Aim Oceanic currents are among the most pervasive hydrodynamic features in shaping community dynamics, population connectivity and phylogeographical structure of intertidal species. Here, we test whether population structure and biogeographical gradients of genetic diversity in the brown alga Sargassum thunbergii are correlated with oceanic currents in the north‐west Pacific ( NWP ). Location North‐west Pacific (25.07°N–43.36°N). Methods Nuclear internal transcribed spacer‐2 and mitochondrial cox 3 sequences were obtained from 835 and 810 individuals of S. thunbergii respectively. Parsimony networks and phylogenetic trees (maximum parsimony and Bayesian inference) were constructed to evaluate phylogeographical structure. Pairwise F ST estimates and analyses of molecular variance ( AMOVA ) at various hierarchical levels (latitude, longitude, marine provinces, biogeographical basins and zoogeographical zones) were conducted to elucidate population genetic differentiation. migrate software was used to estimate the number of migrants between adjacent populations. Results Several lines of evidence indicate that S. thunbergii is characterized by shallow population structure. Geographical distances do not correlate with population pairwise genetic differentiations. The corridor/stepping‐stone model‐based coalescent analyses reveal high levels of asymmetric gene flow among S. thunbergii populations, with the numbers of migrants largely corresponding to the directions of oceanic current systems in the NWP . Genetic signatures also indicate that Jeju Island, Korea might act as a transition zone for dispersal of S. thunbergii in the NWP driven by the Kuroshio Current, thus facilitating subsequent transportation northward into the Sea of Japan and the Yellow‐Bohai Sea. Main conclusions Population genetic homogeneity in S. thunbergii was mainly structured by oceanic currents rather than palaeoclimatic events. Our study illustrates an important phylogeographical case of how coastal hydrodynamic factors contributed to population connectivity and geographical shifts of genetic diversity for marine organisms without a pelagic stage.

Growth responses of Chondrus ocellatus Holmes (Gigartinales, Rhodophyta) to two endophytes, Mikrosyphar zosterae Kuckuck (Ectocarpales, Ochrophyta) and Ulvella ramosa (N. L. Gardner) R. Nielsen (Ulvales, Chlorophyta) in culture - Cyr Abel Maranguy Ogandaga; Han Gil Choi; Jang Kyun Kim; Ki Wan Nam (Algae, 2016)

Bacterial biogeography influenced by shelf–basin exchange in the Arctic surface sediment at the C hukchi B orderland - Dukki Han; Seung‐Il Nam; Ho Kyung Ha; Hyoungjun Kim; Michael J. Sadowsky; Yoo Kyung Lee; Hor‐Gil Hur (Environmental Microbiology, 2016)
Summary It has been known that continental shelves around the A rctic O cean play a major role in the ventilation of the deep basins as a consequence of shelf–basin exchange. In the present study, we found that bacterial assemblage of the surface sediment was different from that of seawater while seawater harboured local bacterial assemblages in response to the A rctic hydrography. This finding suggests that the Arctic seafloor sediments may have distinctive bacterial biogeography. Moreover, the distribution of bacterial assemblages and physicochemical properties in surface sediments changed gradually from the A rctic continental shelf to deep‐sea basin. Based on the results, bacterial biogeography in the A rctic seafloor sediments may be influenced by winnowing and re‐deposition of surface sediments through the sediment gravity flow. The present study offers a deeper understanding of shelf convection and its role for the construction of bacterial assemblages in the A rctic O cean.

Effects of foliar fertilization containing titanium dioxide on growth, yield and quality of strawberries during cultivation - Hyo Gil Choi; Byoung Yong Moon; Khoshimkhujaev Bekhzod; Kyoung Sub Park; Joon Kook Kwon; Jae Han Lee; Myeong Whan Cho; Nam Jun Kang (Horticulture, Environment, and Biotechnology, 2015)

Effects of wave action and grazers on frond perforation of the green alga, Ulva australis - Han Gil Choi; Bo Yeon Kim; Seo Kyoung Park; Jin Suk Heo; Changsong Kim; Young Sik Kim; Ki Wan Nam (Algae, 2015)

New records of three endophytic green algae from Grateloupia spp. (Rhodophyta) in Korea - Chansong Kim; Young Sik Kim; Han Gil Choi; Ki Wan Nam (Algae, 2014)

Oseltamivir-resistant influenza viruses isolated in South Korea from 2005 to 2010 - Han-Gil Cho; Jang-Hoon Choi; Hyun-Kyung Lee; Su-Kyoung Mun; Jong-Bok Lee; Eek-Hoon Jho; Chun Kang; Young-Hee Lim (Archives of Virology, 2013)

High prevalence of amantadine-resistant influenza A virus isolated in Gyeonggi Province, South Korea, during 2005–2010 - Han-Gil Cho; Jang-Hoon Choi; Woon-Ho Kim; Hae-Kun Hong; Mi-Hye Yoon; Eek-Hoon Jho; Chun Kang; Young-Hee Lim (Archives of Virology, 2013)

Morphological and biochemical differences in three Undaria pinnatifida populations in Korea - Kwang-Jae Park; Bo-Yeon Kim; Seo-Kyoung Park; Jong-Hwa Lee; Young-Sik Kim; Han-Gil Choi; Ki-Wan Nam (Algae, 2012)

Macroalgal species composition and seasonal variation in biomass on Udo, Jeju Island, Korea - Jeong-Chan Kang; Han-Gil Choi; Myung-Sook Kim (Algae, 2011)

AAPS Workshop Report: Strategies to Address Therapeutic Protein–Drug Interactions during Clinical Development - Sandhya Girish; Steven W Martin; Mark C Peterson; Lei K. Zhang; Hong Zhao; Joseph Balthasar; Raymond Evers; Honghui Zhou; Min Zhu; Lewis Klunk; Chao Han; Eva Gil Berglund; et al. (The AAPS Journal, 2011)

Effects of temporary and periodic emersion on the growth of Fucus spiralis and Pelvetia canaliculata germlings - Bo-Yeon Kim; Seo-Kyoung Park; Trevor A. Norton; Han-Gil Choi (Algae, 2011)

Antioxidant and Antimicrobial Activity of Zostera marina L. Extract - Han-Gil Choi; Ji-Hee Lee; Hyang-Ha Park; Fotoon A.Q. Sayegh (Algae, 2009)

Temporal Variations in Seaweed Biomass in Korean Coasts: Woejodo and Jusamdo, Jeonbuk - Han-Gil Choi; Ki-Hun Lee; Xiao Qin Wan; Hyun-Il Yoo; Hyang-Ha Park; Jeong-Ha Kim; Ik-Kyo Chung (Algae, 2008)

Physiological differences in the growth of Sargassum horneri between the germling and adult stages - Han Gil Choi; Ki Hoon Lee; Hyun Il Yoo; Pil Jun Kang; Young Sik Kim; Ki Wan Nam (Journal of Applied Phycology, 2008)

Effects of Thermal Effluents from Wolseong Nuclear Power Plant on Macroalgal Composition and Community Structure - Han-Gil Choi (Algae, 2008)

Seasonal Community Structure and Vertical Distribution of Medicinal Seaweeds at Kkotji in Taean Peninsula, Korea - Ki-Hun Lee; Hyun-Il Yoo; Han-Gil Choi (Algae, 2007)

A peroxisome-proliferator activated receptor-γ ligand could regulate the expression of leptin receptor on human hepatic stellate cells - Jung Il Lee; Yong-Han Paik; Kwan Sik Lee; Jin Woo Lee; Yong Soo Kim; Seok Jeong; Kye Sook Kwon; Dong Haeng Lee; Hyung Gil Kim; Yong Woon Shin; Min Ah Kim (Histochemistry and Cell Biology, 2007)

Growth and reproductive patterns of Undaria pinnatifida sporophytes in a cultivation farm in Busan, Korea - Han Gil Choi; Young Sik Kim; Soon Jeong Lee; Ki Wan Nam (Journal of Applied Phycology, 2007)

A phosphate starvation-induced acid phosphatase from Oryza sativa: phosphate regulation and transgenic expression - Yeon Jae Hur; Han Gil Lee; Eun Ji Jeon; Yun Young Lee; Min Hee Nam; Gihwan Yi; Moo Young Eun; Jaesung Nam; Jai Heon Lee; Doh Hoon Kim (Biotechnology Letters, 2007)

Enhanced brain targeting efficiency of intranasally administered plasmid DNA: an alternative route for brain gene therapy - In-Kwon Han; Mi Young Kim; Hyang-Min Byun; Tae Sun Hwang; Jung Mogg Kim; Kwang Woo Hwang; Tae Gwan Park; Woon-Won Jung; Taehoon Chun; Gil-Jae Jeong; Yu-Kyoung Oh (Journal of Molecular Medicine, 2006)

Effects of daylength, irradiance and settlement density on the growth and reproduction of Undaria pinnatifida gametophytes - Han Gil Choi; Young Sik Kim; Soon Jeong Lee; Eun Jeong Park; Ki Wan Nam (Journal of Applied Phycology, 2005)

Genetic engineering of drought-resistant tobacco plants by introducing the trehalose phosphorylase (TP) gene from Pleurotus sajor-caju - Sang-Eun Han; Sang-Ryeol Park; Hawk-Bin Kwon; Bu-Young Yi; Gil-Bok Lee; Myung-Ok Byun (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Competition and facilitation between germlings of Ascophyllum nodosum and Fucus vesiculosus - Han Gil Choi; Trevor A. Norton (Marine Biology, 2005)

Competitive interactions between two fucoid algae with different growth forms, Fucus serratus and Himanthalia elongata - Han Gil Choi; Trevor A. Norton (Marine Biology, 2005)

The Potential use of a Viral Coat Protein Gene as a Transgene Screening Marker and Multiple Virus Resistance of Pepper Plants Coexpressing Coat Proteins of Cucumber Mosaic Virus and Tomato Mosaic Virus - Ryoung Shin; Jung-Heon Han; Gil-Je Lee; Kyung-Hee Peak (Transgenic Research, 2002)

Insulin-induced maturation of Xenopus oocytes is inhibited by microinjection of a Brassica napus cDNA clone with high similarity to a mammalian receptor for activated protein kinase C - June Myoung Kwak; Sun A. Kim; Sung Kuk Lee; Sung- Aeong Oh; Chang- Hyoun Byoun; Jin- Kwan Han; Hong Gil Nam (Planta, 1997)